Particle swarm optimization (PSO)-based clustering algorithm for handwritten digits recognition [electronic resource] - 251539 Nasser Omer Sahel Ba-Karait (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Komputer Sains)) - Universiti Teknologi Malaysia, 2007